The effect of customer engagement on repurchase intention among Indonesia’s digital banks - Kwee, Evan Ariestine Nathanael; Aruan, Daniel Tumpal Hamonangan (Jurnal Ekonomi dan Bisnis, 2024)
A new era of banking in Indonesia has arrived with digital transformation in the banking sector. Digital banks are the main choice of young people, especially millennials and Generation Z. How to choose the ideal digital bank? This research tries to answer the question by understanding the role of customer engagement on repurchase intention. The author connects digital bank applications with customer satisfaction and customers will be committed to attaching themselves to the selected digital bank application. The author uses structural equation modeling (SEM) to test the research model with a sample of millennial and Generation Z customers (n = 200). The study results show a significant positive influence of customer satisfaction on customer engagement and repurchase intention of this generation of customers. These findings can provide input for application development and marketing strategies that suit customers, especially millennials and Z generations. Other digital application companies in Indonesia can conclude what the expectations of millennial and Generation Z customers are. To the author's knowledge, there have not been many articles discussing digital banks, the relationship between application use which is an antecedent effect on customer satisfaction, and the effect of customer engagement on repurchase intention in Indonesia.